Pengaruh Pemasaran Menggunakan Media Sosial Terhadap Kepuasan Pembelian Produk Es Teh Poci - Etty Zuliawati Zed; Affan Miftakhur Royan; Ega Radiansyah; Raihan Fatsa Alfarizi (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
In today's digital era, the role of social media in marketing has become increasingly significant, but there is still a lack of research exploring its influence on traditional products such as iced tea poci. Marketing strategy is a method of generating profits and goals. By improving the products the company sells. This strategy is one of the marketing mix strategies that companies often consider. This Poci iced tea UMKM was founded in 2022 and is located in the Pelita Bangsa University canteen. The aim of this research is to examine the influence of social media and price on purchasing decisions for iced tea pots, both partially and simultaneously. A quantitative research approach is applied in this research which focuses on a causal approach. Determining the sample used was through incidental/accidental sampling techniques. Data from 100 respondents was collected using a questionnaire as a data collection instrument and to analyze the data, multiple linear regression analysis techniques were used. The results of this study show that (1) social media has a positive and significant effect on the decision to purchase iced tea teapots (2) price has no effect on the decision to purchase iced tea pots (3) social media and price have a significant effect on the decision to purchase iced teapots. These results indicate that the marketing mix and marketing strategy are very important in driving sales of the Teh Poci beverage business.